Terra Natal, de Ferreira Itajubá, e a permanência do romantismo - Pinheiro, Mayara Costa (2012)
In this dissertation we argue that the work Terra Natal, by the poet Ferreira Itajubá, presents, predominantly, themes and forms typical of the Romantic period, although it came out in 1914, when the romantic aesthetic was no longer popular in Brazilian Literature. Firstly, we discuss about Ferreira Itajubá s biography, his bibliographic production as well as the critical fortune of his works. Secondly, we outline the course of the Romantic Movement from its emergence in Europe to its arrival in Brazil as well as its impact in the state of Rio Grande do Norte. Finally, we analyze of Terra Natal, taking into account other aspects such as context and structure through the analysis of the poems VII, IX, XVIII, XXI and also of the song Viola , inserted in the poem VIII. We highlight the following romantic themes during the analysis: exile, nostalgia for the past, cult of native land, the romantic view of woman, projection of soul s state on nature, and religiosity. We will try to create dialogues between Terra Natal and works of popular Romantic Brazilian writers, such as Gonçalves Dias, Casimiro de Abreu, José de Alencar,Visconde de Taunay and Castro Alves, in order to show the affiliation of the above-referenced work and the Romantic ideals